2021 DORIS definition of remission in SLE: final recommendations from an international task force - van Vollenhoven, Ronald F; Bertsias, George; Doria, Andrea; Isenberg, David; Morand, Eric; Petri, Michelle A; Pons-Estel, Bernardo A; Rahman, Anisur; Ugarte-Gil, Manuel Francisco; Voskuyl, Alexandre; Arnaud, Laurent; Bruce, Ian N; et al. (Lupus science & medicine, 2021)
ObjectiveTo achieve consensus on a definition of remission in SLE (DORIS).BackgroundRemission is the stated goal for both patient and caregiver, but consensus on a definition of remission has been lacking. Previously, an international task force consisting of patient representatives and medical specialists published a framework for such a definition, without reaching a final recommendation.MethodsSeveral systematic literature reviews were performed and specific research questions examined in suitably chosen data sets. The findings were discussed, reformulated as recommendations and voted on.ResultsBased on data from the literature and several SLE-specific data sets, a set of recommendations was endorsed. Ultimately, the DORIS Task Force recommended a single definition of remission in SLE, based on clinical systemic lupus erythematosus disease activitiy index (SLEDAI)=0, Evaluator’s Global Assessment <0.5 (0–3), prednisolone 5 mg/day or less, and stable antimalarials, immunosuppressives, and biologics.ConclusionThe 2021 DORIS definition of remission in SLE is recommended for use in clinical care, education, and research including clinical trials and observational studies.